Biomedical factors associated to high fertility at high altitude - Gonzales, Gustavo F.; Villena, Arturo (Acta Andina, 2025)
The present study has been desingned to analyze information from the National Peruvian Census, 1993, and the Demographic Survey, 1991-1992 carried out in Peru (Peru, 1994; Endes, 1992) to determine population size at high altitude and Global Fertility Rate. The study has been also designed to investigate in populations living at sea level and at high altitude, age at menarche and age at menopause, the pregnancies during breast feeding in women who never use modern contracepctives, and the serum prolactin levels during first three post partum months in women during breast feeding. Lenght of reproductive life (years) was significantly higher al sea level than at high altitude. The highest the altitude of residence, the lowest the reproductive life span. The adminitrative regions located al high altitude, except Arequipa, have high Global Fertility Rates than populations living at the coast of Peru (La Libertad, Grau and Lima). The three regions located al the jungle of Peru have also high GFR. The GFR according natural geographical regions were 2.1 children per woman in Metropolitan Lima, 3.3 in the rest of the coast, 4.9 in altitude, and 5.1 in the jungle. In 224 mothers who never used modern contraceptivemethods, interval between briths was significantly lower al Cerro de Pasco (2.7 ± 0.15 years) than at Cusco (3.1 ± 0.29 años) (3.1 ± 0.29 years) or Lima (3.8 ± 0.36 years). The percentage of women who got pregnant during breastfeeding increased as it increased the altitude of residence. Serum prolactin levels were significantly higher in women natives at sea level than at high altitude (P < 0.01). In conclusion our data suggest that women at high altitude have more reproductive efficiency.